Shakir M. Pashov. History of the Gypsies in Bulgaria and Europe: Roma - Marushiakova, Elena; Popov, Vesselin; Kovacheva, Lilyana (Brill, 2023)
The publication of this outstanding book marks the beginning of the Brill book series Roma History and Culture. The core of the present volume is an until now unpublished manuscript by Shakir Pashov (1898-1981), a Bulgarian Roma activist whose name continues to be surrounded by rumours and myths. The volume includes the original manuscript of Shakir Pashov on the history of the Gypsies in Europe, followed by archival documents highlighting his life and work, and the text of the first booklet devoted to him, which was the first attempt to create a Roma historical narrative. There is also included an extended biography of Shakir Pashov as known by now. The book contributes to identifying and highlighting the numerous inputs Roma have had to shape their activism and popularise their historical knowledge. Pashov's manuscript is a prominent example of these efforts.